School Readiness in Implementing the Independent Learning Curriculum at SMP Islam Yaqin 1 Montong Batu Bawi, Jerowaru District - Nasrullah, Nasrullah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
The curriculum plays a holistic function in the world of education. In its strategic position, it serves as a vehicle and medium for the conservation, internalization, crystallization, and transformation of knowledge, technology, arts, and human life values. The objectives of this research are: 1) To understand the efforts of schools in implementing the Merdeka Belajar curriculum at SMPI Yaqin 1 Montong Batu Bawi Jerowaru; 2) To identify the roles of teachers in implementing the Independent Learning Curriculum at SMPI Yaqin 1 Montong Batu Bawi Jerowaru; and 3) To analyze the supporting and inhibiting factors in the implementation of the Independent Learning Curriculum at SMPI Yaqin 1 Montong Batu Bawi Jerowaru. The research method used in this study is descriptive qualitative. Data collection techniques involve observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The findings of this study indicate that: 1) the efforts made by the school are not only focused on students but also include curriculum analysis, identification of student needs, competency-based learning design, use of digital resources, innovation in learning approaches, diverse material development, trial and evaluation, up to reflection and adjustment; 2) The teacher council at SMPI Yaqin 1 Montong Batu Bawi, Jerowaru, has played roles as facilitators in facilitating the learning process, evaluators in assessing student progress and educational programs, innovators in creating new learning methods, and motivators in inspiring and encouraging student learning enthusiasm; 3) There are several supporting factors in implementing the Independent Learning Curriculum at this school, including adequate technology infrastructure, education management information systems, competency training and development, supportive leadership, and partnerships with external parties. The inhibiting factors include limited access and infrastructure, data analysis incapacity, time and resource constraints, policy uncertainty, and privacy and security issues. The implications of these findings highlight the importance of continuous support and a holistic approach in ensuring the successful implementation of the Independent Learning Curriculum at the junior high school level, as a step towards improving the quality of education in Indonesia.